Why so slow? - Podreka, Jasna (Annales. Series historia et sociologia, 2024)
Research on sexual harassment and gender-based violence in academia shows that these issues are widespread and complex and that victims face significant barriers, often resulting in under-reporting and cases remaining unresolved. In Slovenia, these issues have received less attention compared to other forms of gender-based violence, resulting in a lack of research, public debate and systematic regulation. A research project funded by the Ministry of Education and the Slovenian Research Agency aimed to investigate how Slovenian academic institutions deal with sexual violence and harassment. The project found a general lack of comprehensive policies and highlighted the need for more proactive measures to effectively address these issues. The results of the project, which are presented in this article, provide insights into the prevalence, regulation and institutional responses to sexual violence and harassment in Slovenian higher education.
Keywords: akademsko okolje; pravni dokumenti; Slovenija; spolno nadlegovanje; spolno nasilje; vsebinska analiza